Study on the Kinematics Analysis and Simulation of Space Octahedron Rolling Robot - Han Shukui; Liu Hongwei; Zhao Zikai; Su Zesheng (Jixie chuandong)
A robot with rolling ability based on spatial octahedron,which consists of 6 vertex modules,12 telescopic unit expansion modules and 1 load module is designed. In order to controlling the robot to roll in a particular direction,the system changes the center of gravity by controlling the amount of expansion and contraction quantity between the telescopic rods. In this study,the process of forward kinematics solution and inverse kinematics solution of the robot are analyzed. According to the analysis,by using the ADAMS software,the dynamic simulation of the movement of the robot,which contain the simulation for gait planning and climbing obstacle capability is finished. Through the result of the dynamic simulation,the correctness of kinematics analysis is validated,and the motion curve of the robot vertices and the centroid is also obtained. The method and simulation results of the kinematics analysis of this study provide an important basis for the optimization design of the space polyhedron rolling robot.